Metodologi Tafsir Al Wasit: (Sebuah Karya Besar Syaikh Muh. Sayyid Tantawi) - Fithrotin Fithrotin (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2018)
The subject matter discussed in this research is how the methodology and style of al-Tafsir al-Wasit li al-Qur'an al-Karim by MuhammadSayyid Tantawi. The main issues are spelled out into several sub-issues, as follows: (1) How is the methodology of Muhammad Sayyid Tantawi in al-Tafsir al-Wasit li al-Qur'an al-Karim? (2) What is the view of Shaykh Muhammad Sayyid Tantawi in interpreting the verses of pluralism? The aim of this research is to know the methodology of writing al-Tafsir al-Wasit li al-Qur'an al Karim by Muhammad Sayyid Tantawi, revealing the essence of pluralism, its principles and the role of Shaykh Muhammad Sayyid Tantawi in interpreting the verses related verses. This research is library research with qualitative analisidata. The research method used, namely: (a) Descriptive study (bahs\taswiri) and (b) Explorative research (bahs\kasyfi). The research approach used is approach of tafsiri and historical approach. The sources of dataprimer in this study are the verses of the Qur'an which speak of the government in al-Tafsir al-Wasit li al-Qur'an al-Karim. The secondary data source is the complementary data needed to interpret the principal data, such as the hadith texts, and the data pertaining to the research that has been studied, whether in the form of scientific papers or books. The collected data is then processed by using comparative method with analysis technique is (content analysis). The results showed that the methodology of writing al-Tafsir al-Wasit li al-Qur'an al-Karim based on tahlili method so that impressed subjective. He relates it to the verses of the Qur'an and the Hadiths of the Prophet and the opinions of the Companions and the Tabi'in. In addition, the privilege of this commentary is the clustering of several verses according to the similarity of the theme by using simple and simple interpretive language. The social style (Ijtima'i) appears in this tafsir. decide) kalam-kalam Allah swt. in the area of ​​his government. This study implies the need for a correct and comprehensive understanding of pluralism and others according to the Qur'an.